2023
DOI: 10.1038/s41598-022-26349-x
|View full text |Cite|
|
Sign up to set email alerts
|

A joinpoint and age–period–cohort analysis of ocular cancer secular trends in Iran from 2004 to 2016

Abstract: Investigating secular trends of ocular cancer registration in Iran. After acquiring Iranian national population-based cancer registry data, trends of age-standardised incidence rates (ASIR) of ocular cancers and annual percent changes (APC) between 2004 and 2016 were analysed in age groups, gender, topography and morphology types with joinpoint regression analysis. Age, period, and cohort effects on incidence rates were estimated by age–period–cohort model. Geographic distribution of ASIR was assessed using GI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…A large number of studies have been conducted both domestically and internationally using the JPR model and the APC model to determine the prevalence of chronic non-communicable diseases, which can also be used to predict the future burden of cancers ( 7 11 ). Research reported that the death rate of liver cancer in both sexes in Korea has decreased gradually since 1993, with the cohort effect primarily responsible for this trend, which was consistent with the trend of liver cancer mortality in Serbia during 1991~2015 and Mexico during 1998~2018 ( 12 14 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A large number of studies have been conducted both domestically and internationally using the JPR model and the APC model to determine the prevalence of chronic non-communicable diseases, which can also be used to predict the future burden of cancers ( 7 11 ). Research reported that the death rate of liver cancer in both sexes in Korea has decreased gradually since 1993, with the cohort effect primarily responsible for this trend, which was consistent with the trend of liver cancer mortality in Serbia during 1991~2015 and Mexico during 1998~2018 ( 12 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…A large number of studies have been conducted both domestically and internationally using the JPR model and the APC model to determine the prevalence of chronic non-communicable diseases, which can also be used to predict the future burden of cancers (7)(8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%